ChemInform Abstract: Hydrosilylation of Internal Alkynes Catalyzed by Tris‐Imidazolium Salt‐Stabilized Palladium Nanoparticles. Issue 31 (5th August 2014) - Planellas, Marc; Guo, Wusheng; Alonso, Francisco; Yus, Miguel; Shafir, Alexandr; Pleixats, Roser; Parella, Teodor
Abstract Optimized reaction conditions render possible the stereoselective hydrosilylation of internal alkynes to form (E)‐vinylsilanes.